2005
DOI: 10.1074/jbc.m501206200
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of the Apoptosis Inhibitor DIAP1 by the Apical Caspase DRONC in Both Normal and Apoptotic Drosophila Cells

Abstract: In Drosophila S2 cells, the apical caspase DRONC undergoes a low level of spontaneous autoprocessing. Unintended apoptosis is prevented by the inhibitor of apoptosis DIAP1, which targets the processed form of DRONC for degradation through its E3 ubiquitin protein ligase activity. Recent reports have demonstrated that shortly after the initiation of apoptosis in S2 cells, DIAP1 is cleaved following aspartate residue Asp-20 by the effector caspase DrICE. Here we report a novel caspase-mediated cleavage of DIAP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Needless to say that the double mutant I393A,D20A was also unstable (lanes 10-12), and its degradation was proteasome-dependent ( Figure 3cii). Assuming that other, yet to be discovered cleavages can also lead to subsequent degradation of the cleaved product (see for example, Muro et al 34 ), it was important to test whether the RING finger domain can be involved in the degradation of Figure 3 Processing of DIAP1 is not essential for its degradation and does not require its RING finger domain. (a) DIAP1 is rapidly degraded in the presence or absence of caspase inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Needless to say that the double mutant I393A,D20A was also unstable (lanes 10-12), and its degradation was proteasome-dependent ( Figure 3cii). Assuming that other, yet to be discovered cleavages can also lead to subsequent degradation of the cleaved product (see for example, Muro et al 34 ), it was important to test whether the RING finger domain can be involved in the degradation of Figure 3 Processing of DIAP1 is not essential for its degradation and does not require its RING finger domain. (a) DIAP1 is rapidly degraded in the presence or absence of caspase inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…35,36 Treatment of Drosophila SL2 cells with apoptotic stimuli results in rapid removal of full-length DIAP1 protein 35,37 and this degradation is delayed by addition of the proteosome inhibitor MG132. 37 We have used BG2 cells and confirmed that following treatment with cycloheximide, endogenous DIAP1 protein is degraded in 4 h, concurrent with cleavage of DRONC and DRICE processing at 6 h ( Figure 1b). We used MG132 to assess the effect of sustained DIAP1 protein levels on caspase activation.…”
Section: Resultsmentioning
confidence: 99%
“…This has been demonstrated previously on synthetic peptidyl substrates, 16 and also in terms of its autolytic cleavage and cleavage of Drosophila IAP1. 14,16,25 Interestingly, as shown in Figure 4a, caspase-9 also tolerates Glu in its primary specificity pocket, and can cleave its own inter-chain segment following a Glu residue, although this cleavage is subservient to the natural Asp cleavage sites in the caspase-9 linker. 26,27 We demonstrate, using a matched set of substrates, that DRONC may have almost equal activity on tetrapeptides containing Asp and Glu in P1, but this does not hold for a downstream substrate.…”
Section: Discussionmentioning
confidence: 99%